XFEM for Fracture Analysis in 2D Anisotropic Elasticity (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, a method is proposed for extracting fracture parameters inanisotropic thermoelasticity cracking via interaction integral method within the frameworkof extended finite element method (XFEM). The proposed method is applied tolinear thermoelastic crack problems. The numerical results of the stress intensity factors(SIFs) are presented and compared with those reported in related references. Thegood agreement of the results obtained by the developed method with those obtainedby other numerical solutions proves the applicability of the proposed approach andconfirms its capability of efficiently extracting thermoelasticity fracture parameters inanisotropic materials.